INFLUENCE OF PROBLEM POSING METHOD ON PROBLEM SOLVING SKILLS - Daryati, Dewi (JURNAL PENDIDIKAN ILMU SOSIAL, 2018)
This study aims to analyze the difference between problem-solving ability using problem posing method and conventional method. This research was conducted at SMAN 1 Parongpong Kabupaten Bandung Barat. The research subjects were students of class X Social Major. The research method used quasi experiment to know the effect of treatment. The result of data analysis shows that there is a significant difference between problem solving ability among students using problem posing method and conventional method on Economic Subjects (Market Chapter: Demand, Supply and Equilibrium Price). Based on research results, it is suggested to use problem posing method to improve problem solving ability in economic learning.